2012
DOI: 10.2147/ijn.s31365
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell specific targeting by the preS1 domain of hepatitis B virus surface antigen displayed on protein nanocages

Abstract: Abstract:Protein nanocages are self-organized complexes of oligomers whose three-dimensional architecture can been determined in detail. These structures possess nanoscale inner cavities into which a variety of molecules, including therapeutic or diagnostic agents, can be encapsulated. These properties yield these particles suitable for a new class of drug delivery carrier, or as a bioimaging reagent that might respond to biochemical signals in many different cellular processes. We report here the design, synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Different research groups have mapped the HBV preS1 domain involved in receptor recognition but the HBV preS1 region between residues 21–47 is considered crucial for attachment and uptake of the virions into the hepatocytes 15 16 18 19 . A peptide spanning this pre-S1 region has been used as a hepatocyte targeting agent and demonstrated to inhibit viral binding to human hepatic cells 42 . PreS1 (21–47 a.a.)-specific antibodies have been shown to be effective in prevention of hepatitis B infection in non-human primates (NHPs).…”
Section: Discussionmentioning
confidence: 99%
“…Different research groups have mapped the HBV preS1 domain involved in receptor recognition but the HBV preS1 region between residues 21–47 is considered crucial for attachment and uptake of the virions into the hepatocytes 15 16 18 19 . A peptide spanning this pre-S1 region has been used as a hepatocyte targeting agent and demonstrated to inhibit viral binding to human hepatic cells 42 . PreS1 (21–47 a.a.)-specific antibodies have been shown to be effective in prevention of hepatitis B infection in non-human primates (NHPs).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that N‐terminal myristoylation of preS1 was very important for its binding to receptors on the membrane of hepatic cells . But some researchers also got controversial results and found that naked preS1 also had the ability to recognize receptors . In this paper, we used the naked preS1 peptide without myristoylation modification and achieved a satisfying result.…”
Section: Discussionmentioning
confidence: 95%
“…Animal models are an obstacle in HBV research involving the natural infection course. Extensive efforts have been put forth in this field . The chimpanzee is a good research model for HBV, but its broad range of application is limited by the high cost and resource.…”
Section: Discussionmentioning
confidence: 99%
“…Also, for in vivo application, specific drug delivery to target cells was very important in order to avoid any undesirable side effects. An advantage of Hsp cages is that the peptide ligand can be modified by the chemical/genetic method, 22,23 enabling the delivery of cytotoxic reagents to specific cells. It was previously reported that Hsp cages could specifically target human hepatoma cells after binding human hepatoma binding peptides (SP94 peptides) to the surface of the Hsp cages using poly(ethylene glycol) linkers.…”
Section: Future Plansmentioning
confidence: 99%
“…Hsp cages have also been used for biomedical applications due to their advantageous biocompatibility, biodegradability, and easy fabrication through chemical/genetic strategies. [22][23][24][25] Although Hsp cages have several favorable characteristics making them suitable as drug carriers, to the best of the authors' knowledge, only a few reports have examined this possibility. 11 In this study, an Hsp cage-based prodrug was developed.…”
Section: Introductionmentioning
confidence: 99%